Foundations of the Islamic State Management, Money, and Terror in Iraq, 2005-2010 - Johnston, Patrick B. (RAND Corporation, 2016)
Drawing from 140 recently declassified documents, this report comprehensively examines the organization, territorial designs, management, personnel policies, and finances of the Islamic State of Iraq (ISI) and al-Qa'ida in Iraq. Analysis of the Islamic State predecessor groups is more than a historical recounting. It provides significant understanding of how ISI evolved into the present-day Islamic State and how to combat the group.